The influence of partial or total thymectomy during open heart surgery in infants on the immune function later in life - EYSTEINSDOTTIR, J H (Blackwell Science Inc, 2004)
Infants undergoing open heart surgery often have all or part of their thymus removed. The activity of the immune system has not been investigated thoroughly in these children, and only shortly after the operation. Therefore, it was decided to investigate the activity of the immune system in more detail in children several years after their operation. Peripheral blood samples from 19 children who had undergone open heart surgery during their first months of life was collected (study group) and from 19 age- and gender-matched children (control group). The activity of the immune system was evaluated by measuring the number of different cell types in peripheral blood, the phenotype of lymphocytes and the response of T cells following in vitro stimulation by mitogen, tetanus toxoid and measles antigen. The study group had significantly lower counts of total lymphocytes, which was reflected in a lower number of T cells but not B cells. Furthermore, the study group had significantly lower proportion of T cells (CD3(+)) and helper T cells (CD4(+)), but not cytotoxic T cells (CD8(+)). The level of neutrophils in peripheral blood was significantly higher in the study group. This may indicate enhanced innate immunity when the acquired immunity is defective. The results indicate a shift to extrathymic T cell maturation, which is less efficient for CD4(+) helper cells than for CD8(+) cytotoxic cells.